1995
DOI: 10.1097/00005392-199507000-00054
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Lower Urinary Tract Abnormalities and Disease-Related Parameters in Multiple Sclerosis

Abstract: Multiple sclerosis affects the lower urinary tract in many patients. The relationship between lower urinary tract abnormalities and disease-related parameters of multiple sclerosis is not well described. We screened urologically and neurologically 212 patients according to a standard protocol. Micturition complaints were noted in 52% of the patients and urodynamic abnormalities were found in 64%. A statistical correlation was found between detrusor hyperactivity and detrusor hypoactivity with disease-related p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
1
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 26 publications
0
42
1
3
Order By: Relevance
“…7,11,14 Our ®ndings con®rm a statistically signi®cant positive relationship between disease duration and micturition complaints 7 (Table 2). On the other hand, we did not ®nd a signi®cant relation between lower urinary tract symptoms and the disability status, when considering four classes of patients, each including two groups, according to the Kurtzke disability status scale (Table 2).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…7,11,14 Our ®ndings con®rm a statistically signi®cant positive relationship between disease duration and micturition complaints 7 (Table 2). On the other hand, we did not ®nd a signi®cant relation between lower urinary tract symptoms and the disability status, when considering four classes of patients, each including two groups, according to the Kurtzke disability status scale (Table 2).…”
Section: Discussionmentioning
confidence: 53%
“…Some authors 14 have already reported that multiple sclerosis patients with a short disease duration can su er from serious voiding problems, but usually micturition problems appear related to the disability status. 7,11,14 Our ®ndings con®rm a statistically signi®cant positive relationship between disease duration and micturition complaints 7 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the bladder dysfunction that follows spinal cord injury and causes life-threatening upper urinary tract conditions, MS very rarely causes severe upper urinary tract involvement but rather results in morbidity that influences the quality of life [9].…”
Section: Discussionmentioning
confidence: 99%
“…24 In previous studies a statistical correlation was found between detrusor hyperactivity or detrusor hypoactivity with disease duration, disability and neurophysiological ®ndings. 26 Cortical evoked potentials following stimulation of the pudendal nerve were delayed in a high percentage of MS patients with bladder dysfunction, 27 however the real impairment rate of the pSEP is at present not well known in early stages of MS. Classical multimodality evoked potentials recorded in our patients showed an abnormality rate of 68.7%.…”
Section: Discussionmentioning
confidence: 99%